Safety Management In Emergency Situations: Implementation of The Apell Method - Marian KOPCZEWSKI; Grzegorz WISNIEWSKI; Robert SADOWSKI (Communications of International Proceedings, 2024)
The research problem was to obtain an answer on how to design a coherent system of response to emerging threats, taking into account the current legal status of the country in the system of the statutory regime of European Union standards in the context of disasters, failures, and other unfavorable, unforeseen events. At the same time, the authors note the lack of a legal concept as well as the lack of discussion of insufficient legal acts in scientific articles, thus a kind of gap appears, i.e. space giving the potential to establish new legal acts or expand the existing ones. It is worth pointing out the need, according to researchers, to develop rescue plans for municipalities and poviats, as well as informing the population about potential threats in a structured and consistent manner with high effectiveness. The research methods used related to the analysis of the content of monographs, legal acts, scientific periodicals and programs resulting in reports on implemented projects and undertakings. The increasing use of hazardous chemicals in industry, commerce and transport – combined with the potential for misuse by terrorists – has increased the risks to workers and local communities. To address these threats, the United Nations Environment Program (UNEP) launched the APELL (Local Emergency Awareness and Preparedness) program in 1988. Developed in response to multiple chemical accidents with devastating human, environmental and economic impacts, the goal of APELL is to: improve community safety and preparedness by increasing awareness and establishing emergency protocols at the local level.
Keywords: emergency process; security; crisis situations; terrorism